2011
DOI: 10.2147/tcrm.s6769
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of acute otitis externa with ciprofloxacin otic 0.2% antibiotic ear solution

Abstract: Background/objectiveAn inflammation of the cutis and subcutis of the external auditory canal is a primary symptom in cases of acute otitis externa. It is usually treated locally, since this type of therapy ensures a high concentration of the drug and interacts at the site of inflammation with no systemic effects. This systematic review compares the efficacy of treatment using a ciprofloxacin 0.2% solution with other therapeutic options.MethodsAfter compiling a catalog of search terms, medical databases were se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 14 publications
(41 reference statements)
3
24
0
1
Order By: Relevance
“…41 In conclusion, the combination of an antibiotic (ciprofloxacin) with a corticosteroid (fluocinolone acetonide) constitutes a safe and effective treatment for diffuse otitis externa. The low rate of adverse events described for ciprofloxacin was also confirmed in the previously mentioned systematic review, including eight studies with ciprofloxacin where the low rate of side effects and the good safety profile were highlighted.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…41 In conclusion, the combination of an antibiotic (ciprofloxacin) with a corticosteroid (fluocinolone acetonide) constitutes a safe and effective treatment for diffuse otitis externa. The low rate of adverse events described for ciprofloxacin was also confirmed in the previously mentioned systematic review, including eight studies with ciprofloxacin where the low rate of side effects and the good safety profile were highlighted.…”
Section: Discussionmentioning
confidence: 97%
“…36,41 A recent systematic review of 14 randomised controlled studies in acute otitis externa, 8 of them using ciprofloxacin 0.2 and 0.3 per cent solutions, demonstrated the non-inferiority of ciprofloxacin in the treatment of otitis externa, in terms of cure rate and microbiological eradication, compared to a combination of polymyxin B, neomycin sulphate and hydrocortisone. These results are similar to the microbiological eradication rates found in two other trials with ciprofloxacin plus dexamethasone, which were 86 and 92 per cent vs 84 and 89 per cent for a combination of polymyxin B, neomycin sulphate and hydrocortisone.…”
Section: Discussionmentioning
confidence: 99%
“…This disease has a local inflammation process, but it can diffuse to other tissues if suitable treatment is not started especially in immunosuppressed patients ( 6 , 7 ). Some factors such as moisture, humidity, swimming in the pool, trauma and use of hearing aids can lead people to otomycosis, although there are no exact predisposing factors to be detected after the accurate history and physical examination in some cases ( 8 - 10 ). Otomycosis exists in all ages, especially in middle ages, and also in both genders ( 5 , 11 ), but it is prevalent in swimmers and also with mixed bacterial otitis ( 12 - 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Drehobl et al [12] treated 319 external otitis patients with 0.2% ciprofloxacin for 7 days and 87.5% bacterial eradication was determined for P. aeruginosa. In the evaluation of previous studies, ciprofloxacin topical solution has been shown to have high eradication rates, such as 83.3%-95.7%, against P. aeruginosa [13] . In the ciprofloxacin-treated group in the current study, reproduction was determined in all the smear samples taken on Day 1 of the treatment, and the bacteria eradication rates were found to be 81.25%, 100%, and 100% on Days 4, 7, and 10 respectively.…”
Section: Discussionmentioning
confidence: 99%